2015
DOI: 10.3389/fimmu.2015.00175
|View full text |Cite
|
Sign up to set email alerts
|

Long Intergenic Non-Coding RNAs: Novel Drivers of Human Lymphocyte Differentiation

Abstract: Upon recognition of a foreign antigen, CD4+ naïve T lymphocytes proliferate and differentiate into subsets with distinct functions. This process is fundamental for the effective immune system function, as CD4+ T cells orchestrate both the innate and adaptive immune response. Traditionally, this differentiation event has been regarded as the acquisition of an irreversible cell fate so that memory and effector CD4+ T subsets were considered terminally differentiated cells or lineages. Consequently, these lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 222 publications
(190 reference statements)
0
12
0
Order By: Relevance
“…Some lncRNAs have a critical role in adaptive and innate immunity (31). NeST is one such lncRNA that is well characterized in regard to its role in immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Some lncRNAs have a critical role in adaptive and innate immunity (31). NeST is one such lncRNA that is well characterized in regard to its role in immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Some signals trigger internal circuits that enforce, reinforce, or destabilize T-cell polarization through multiple mechanisms, including epigenetic modifications (Wang et al 2015). MicroRNAs and long noncoding RNAs (lncRNAs) have also been found to control various aspects of CD4 T-cell differentiation and effector function (Baumjohann and Ansel 2013; Panzeri et al 2015).…”
Section: Heterogeneity Of Human Cd4 T Cellsmentioning
confidence: 99%
“…Furthermore, previous studies have identified lncRNAs expressed in B lymphocytes and T lymphocytes development and activation [74,75]. Panzeri et al suggested that long intergenic non-coding RNAs could be novel drivers of human lymphocyte differentiation [76]. Moreover, previous researches performed RNA sequencing of monocytes from four individuals and combined their data with eleven other publicly available datasets and provided a landscape of lncRNAs in monocytes [77].…”
Section: Lncrnas Involved In Inflammation After Scimentioning
confidence: 99%